Influence of independent bent-up bars on the shear capacity of reinforced concrete beams [electronic resource] - Saleh Abdullah Saleh Baras, 1987- (2013)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2013